Learning Styles and Toxicology Knowledge of Medical Students of Mashhad University of Medical Sciences - Emadzadeh, Ali; Alizadeh, Anahita; Hosseini, Seyed Masoud; Najari, Fares; Najari, Dorsa (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Considering the breadth of medical knowledge, it is very important to study medical students’ learning and ways to facilitate it. One of the key areas in learning is studying methods. This study aimed to determine the preferred learning style in medical students and the level of learning in a medical discipline (Toxicology) as well as its correlates. Methods: Thirty-seven medical students who were admitted to an internship course, completed a questionnaire about their preferred learning style using the VARK (Visual, Auditory, Read/Write and Kinesthetic) method. Then, a standardized test was applied to measure the students’ score for each level of learning and the total score of learning. Results: The study participants included 20 males and 17 females. The preferred style of learning was mostly (32%) aural. Thirteen (35%) students preferred single-style of learning, and 24 (65%) preferred more than one style. No significant relationship was found between the learning style and the score on each learning level. No significant relationship was found between the preferred learning style and the total score of the final test (P>0.05). There was also no significant difference between persons with regard to single style and multiple styles of learning (P=0.46). The scores of theoretical knowledge was higher than the practical knowledge in all styles and among those with a multiple style of learning. Conclusion: Learning style is just one of the effective factors in medical education and it has no significant relationship with the level of learning. The current training method in some areas (toxicology training) for medical students, is more successful in transferring knowledge than skills to apply that knowledge.